Determinación de hemoglobina y hematocrito en pobladores adultos de ambos sexos atendidos en el puesto de salud de Buenos Aires Sur del distrito Víctor Larco, en diciembre 2010” - Urcia Ramírez, Mario Antonio (2011)
In this work is determined hemoglobin (Hb) and hematocrit (Hto) in adults of both sexes who were treated at the Buenos Aires Sur health post, Victor Larco district in December 2010. The sample was 84 persons of both sexes, 65 were females and 19 to males. We proceeded to the blood sampling needle in the cephalic vein of the arm at the elbow flexion, to determine methods of microhematocrit and cyanmethaemoglobin. The results were expressed by age and sex, finding values for hemoglobin: normal values in 84.62% women and 84.21% of males decreased values in the 4.62% women and 10.53% of males, and increased values in 10.77% of 5.26% of women and men. The results in the determination of hematocrit were as follows: normal in 87.69% women and 73.68% of males decreased values in the 7.68% women and 21.05% of males, and increased values in the 4.62% in women and 5.26 % of males. The highest percentages of people in the study were reported normal values for hemoglobin and hematocrit.